Pendidikan Kesehatan Tentang Kesehatan Jiwa Emosional Pada Remaja - Gurning, Maylar; Pademme, Dirgantari; Mansoben, Novita; Manoppo, Inggerid Agnes; Banna, Triani (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2023)
Adolescence is a period marked by biological, psychological, and social development. These changing conditions often result in disharmony, so a balance is needed so that adolescents can achieve adequate and mature psychosocial development in accordance with age-level developments. It is estimated that 1 in 7 children aged 10 to 19 are likely to experience psychological problems. It is unfortunate that this emotional disorder is not recognized and often does not get proper treatment. The determinant of emotional mental symptoms in Indonesia in junior high school students is 60.17% of junior high school students, with the majority being between the ages of 13 and 15 who experience symptoms of mental emotional problems. Symptoms experienced, such as loneliness (44.45%), feeling anxious (40.75%), and even having suicidal ideation (7.33%), Therefore, the provision of related education can provide input and knowledge to adolescents about the benefits of managing emotional and mental health. The method of implementing community service is by giving pre- and post-tests to measure adolescent knowledge about emotional and mental health. The results of this service activity show that there is an increase in knowledge in adolescents before and after being given health education